ETHNO PHARMACOLOGY STUDY, ACUTE AND ANALGESIC BAMBOO LEAVES EXTRACT ETHANOL (BAMBUSA VULGARIS) ENDEMIC PLANT WEST KALIMANTAN - Annafiatuzakiah; Inarah Fajriaty, Rafika Sari, Pratiwi Apridamayanti (CV. Adiba Aisha Amira, 2024)
Objectives: The purpose of this study was to determine the benefits of bamboo leaves as empirically analgesic drugs is safe to eat. Methods: Ethno pharmacology study was see the benefits of bamboo leaves use empirically in the community and continued test of pharmacology, where bamboo leaves were extracted by maceration using 96% ethanol. The results of the extraction continued with pharmacological trials method toxicity test to determine the level of safety of a drug and continued with analgesic test to determine the effective dose in bamboo leaves. Rat wistar were using orally for toxicity tests consist of a dose of 2000mg/kgbwbw and dose of 500mg/kgbw to see the LD50 and continue with test of analgesics use mice strains Swiss consisting the positive control group (Paracetamol 500mg/kgbw), negative control (CMC-Na) and 1 dose (300mg/kgbw), second dose (600mg/kgbw), the third dose (1200mg/kgbw). Research on analgesic test using stretching to give a 0.6% acetic acid intraperitoneally and observed every 5 minutes for 60 minutes, the next is done with the data analysis. Results: Study Ethno pharmacology bamboo leaves empirically used as a pain medication, but clinical use of traditional medicine is not recognized, if not scientifically proven the test of pharmacology to determine efficacy as an analgesic, because not secure, study was conducted determine the lethal dose (LD50) ethanol extract of bamboo leaves use Wistar rats. In the acute toxicity results obtained LD50>5000mg/kgbw and organ index see no effect between the dose of 2000mg/kgbw and 5000mg/kgbw. Further research on analgesic test to determine whether there is the analgesic effect of the ethanol extract of the leaves of bamboo (Bambusa vulgaris) using mice Swiss strain. This study is divided into 5 in the control group positive control (Paracetamol 500mg / kgbw), Negative control (CMC-Na) and Dose 1 (300 mg/ kgbw), Dose II (600mg/kgbw), Dose III (1200 mg/kgbw), Testing the analgesic effect is done by giving chemical stimulation in the form of a 0.6% acetic acid intraperitoneally. The response of mice were observed amount of stretching, observations were made every 5 minutes for 60 minutes. Data were evaluated with SPSS to compare the results from each dose group exhibited significantly with the controls at a rate of 0.05%. Conclusions: The utilization of bamboo leaves empirically showed that bamboo leaves are consumed safely and effectively as a pain medication. The results of this study are supported on the acute toxicity test LD50> 5000mg/kgbw. The next in analgesic trials showed that the ethanol extract of bamboo leaf has efficacy as an analgesic percent protection stretching on the dose I: 71.08%, dose II: 42.85%, dose III: 28.23%.